Resale Maintenance and the Service Argument: Efficiency Effects - Norbert Schulz (University of Würzburg, Department of Economics, 2005)
Proponents of RPM argue that RPM helps to sustain a high level of service at the point of sale and that such a high level is efficient. This paper provides a simple model which leads to the following conclusions: 1) RPM may increase or decrease the level of service. 2) Whether the service level is more efficient under RPM does not depend on the fact that service increases due to RPM. It may be lower under RPM and more efficient. 3) Whether the service level is more efficient depends on the characteristics of the heterogeneous consumers. A feature of the model which deviates from those found in the literature is the introduction of a class of consumers who do not search but decide on a purchase spontaneously.
Keywords: L42; K21; L13; 330; resale price maintenance; service; efficiency; Preisbindung; Kundendienst; Dienstleistungsqualität; Wirtschaftliche Effizienz; Theorie